WATER INHABITING BIRDS OF MAIGANGA POST COAL MINING PONDS AND ARTIFICIAL WETLAND (FUDMA JOURNAL OF SCIENCES, 2024)
Wetlands play a significant role in bird conservation and generally support biological diversity. Historically, bird community assessment has been employed in monitoring and identifying areas for conservation actions. In this study, we examined two post mining ponds and one artificial wetland in Maiganga Coal Mine, Gombe State for wetland avifauna. We focused on water birds (i.e. bird species that depend wholly or partially on water and wetland ecosystems for their survival). Survey was conducted during the onset of dry season in October 2021 to September 2022. Point count technique was used for the survey. A total of 626 individuals of 23 species from 19 genera, 10 families and 6 bird Order were recorded. The White-faced whistling duck was the most abundant bird species and was restricted to the active-mine pond (AMP). AMP was the most diverse of the three water bodies surveyed. However, some species were exclusive to either of the three sites. Similarly, AMP was the most abundant site with 426 individuals from 16 bird species, followed closely by the sedimentation pond with 147 individuals drawn from 15 bird species. The results suggest that water depth, age of establishment and surrounding vegetation structure could be a major determinant of bird species composition and abundance in the study area. The study highlights the importance of restorative actions aimed at recovering modified landscapes, through tree planting and creation of wetlands. This is evident in the presence of waterbirds in Maiganga, a location that was previously devoid of perennial water bodies and...
Keywords: Maiganga; Coal Mine; Water birds; Species diversity; Wetland